Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©: Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ ØªØ±Ø¬Ù…Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØØ§Ù„Ø© Ø¹Ù† Ù†ØªØ§Ø¦Ø¬ ØªØ±Ø¬Ù…Ø§Øª Ø·Ù„Ø§Ø¨ Ù‚Ø³Ù… Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¬Ø§Ù…Ø¹Ø© Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©) - Mahbub Mahbub; Fajar syahrudin (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
This study aims to determine and describe the errors and their causes that occur in the results of the translation carried out by students of the 2016 Arabic Language Education class. The data of this study were obtained from the results of the students' translation which were taken using written test techniques. After the translation results are obtained, the error identification, error classification and error reconstruction are carried out. The forms of errors that occur in the translation results of the students are word choice errors, word omission errors, word addition errors, rule errors, and word form errors. As for the causes of errors, there are two things that underlie the errors found, namely interlingual transfers and intralingual transfers.